Features of creation of documentary and military prose (based on the novel by A. Beck «Volokolamsk highway») - Otesh Ж.Ә.; Myrzakhmetuly М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The novel «Volokolamsk highway» is one of the documentary works that made an outstanding contribution to the formation and development of Kazakh military prose. This military educational work, written on military subjects and recognized by the world, in the distant years of the great Patriotic war drew all the attention of the world to itself. This novel, written with the direct participation of a connoisseur of military science B. Momyshuly, is a large-scale work aimed at revealing the truth and psychology of war. The article deals in detail with the problems of historical personality in military prose and key problems of historical reality